PHARMACEUTICAL DEVELOPMENT AND COMPATIBILITY STUDIES ON CYTARABINE INJECTION - Konda, Noveen; P, Prashanth; G, Arvind; Shah, Sumit (Asian Journal of Pharmaceutical and Clinical Research, 2013)
The aim of present work was to develop a stable Cytarabine injectable formulation for the treatment of various cancers. Cytarabine is freely soluble and stable in water. Different compatibility studies of Cytarabine formulation was carried out. The fluororesin coated chlorobutyl rubber stopper was given least % impurities as compare to bromobutyl and teflon coated rubber stoppers. The platinum cured silicon tubing of Masterflex was observed the best suitable tubing in terms of % impurities. The filter made of the Polyethersulfone (PES) was compatible with Cytarabine formulation in terms of % impurities and loss of drug during filtration. Thermal cycling was performed at 40Â°C for 4 days and there was found that there was no significant decrease in assay and related substances. Filter validation was carried out with PES capsule filter and it was found to be compatible with Cytarabine formulation. Chemical stability of Cytarabine formulation with infusion solutions was performed and (0.9% NaCl, 5% Dextrose & Water) it was observed that the final solution for injection was stable after 5 days. Osmolality of the Cytarabine injection with 0.9% sodium chloride & 5% dextrose was performed and it was found to be optimum for injectable formulation. Â  Key words: Cytarabine, Compatibility, Container closure, Filter validation.